Development of touristic village and creative industry in improving social welfare at Wukirsari Village, Imogiri, Bantul District - Saraswati, Prihatin; Ahmad Puad, Farah Najwa (Asian Journal of Assessment in Teaching and Learning, 2020)
The purpose of this study is to find out the role of development of touristic village and creative industry in improving social welfare on Wukirsari Village, Special Region of Yogyakarta Province (DIY Province). This research used qualitative and descriptive method. The data conveys that the development of touristic village and creative industry in Wukirsari Village brings out positive impact to its social welfare. The development consists of various productions; leather wayang puppet with tatah sungging, wedang uwuh traditional drink, bamboo crafts, and natural-dye batik. In addition, the village has distinct potentials to become a touristic village. Those distinct potentials are originated from its cultural resource, the Mataram kings’ burial ground. The obstacles regarding this research were the coaching of better-quality touristic village development and creative industry people management in order to become a competitive travel destination.